2019
DOI: 10.1128/aac.01931-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Efficacy of Humanized WCK 5222 (Cefepime-Zidebactam) Exposures against Carbapenem-Resistant Acinetobacter baumannii in the Neutropenic Thigh Model

Abstract: Herein, we describe the in vivo efficacy of human-simulated WCK 5222 (cefepime-zidebactam) exposure against carbapenem-resistant Acinetobacter baumannii strains in a neutropenic murine thigh infection model. Five of the six isolates examined expressed OXA-23 or OXA-24. WCK 5222, despite showing MICs of 16 to 64 mg/liter, produced remarkable in vivo activity; human-simulated exposure showed a decline in the bacterial burden for all isolates (mean reduction, Ϫ2.09 Ϯ 1.01 log 10 CFU/thigh), while a lack of activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 12 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…We observed a similar net killing effect, as WCK 5222 achieved 1 to 3 log kill against all MBL-producing Enterobacteriaceae isolates. Additional studies have demonstrated comparable responses in mouse models utilizing the thigh and lung infection models with other GNR, including A. baumannii and P. aeruginosa (28)(29)(30). Similarly to the present study involving strains expressing enzymes that zidebactam do not inhibit (MBL), Almarzoky et al and Avery et al demonstrated a potent zidebactam-mediated enhancing effect on cefepime efficacy against MDR A. baumannii expressing zidebactam noninhibitable carbapenem-hydrolyzing class D enzymes (29,30).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We observed a similar net killing effect, as WCK 5222 achieved 1 to 3 log kill against all MBL-producing Enterobacteriaceae isolates. Additional studies have demonstrated comparable responses in mouse models utilizing the thigh and lung infection models with other GNR, including A. baumannii and P. aeruginosa (28)(29)(30). Similarly to the present study involving strains expressing enzymes that zidebactam do not inhibit (MBL), Almarzoky et al and Avery et al demonstrated a potent zidebactam-mediated enhancing effect on cefepime efficacy against MDR A. baumannii expressing zidebactam noninhibitable carbapenem-hydrolyzing class D enzymes (29,30).…”
Section: Discussionsupporting
confidence: 69%
“…However, BCHs, such as the afore- mentioned zidebactam, were developed because they not only exert ␤-lactamase inhibition but also have a direct antibacterial effect via high-affinity binding to PBP2 (16,17,20). The combination of agents that target PBP3 (cefepime) and PBP2 (zidebactam) has been shown to exhibit enhanced in vitro and in vivo activity compared to cefepime alone (15)(16)(17)(18)(19)(20)(28)(29)(30)(31). In fact, despite the fact that zidebactam possesses no direct inhibitory activity against MBL enzymes, potent activity against MBL-producing organisms has been demonstrated for cefepime with zidebactam, due to the complementary PBP binding activity (15,16,18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Female ICR mice weighing 20 to 22 g (Charles River Laboratories, Inc., Wilmington, MA) were utilized in the study, and the protocol was approved by the Hartford Hospital Institutional Animal Care and Use Committee. The neutropenic murine thigh model was used as previously published (5). Treatment and control groups were composed of three mice each.…”
mentioning
confidence: 99%
“…Many studies demonstrated that the zidebactam-mediated potentiation of cefepime activity against Enterobacterales and P. aeruginosa isolates is manifested by a significant reduction in cefepime MICs ( Barceló et al., 2021 ; Jean et al., 2022 ). On the other hand, against A. baumannii isolates, such enhancement in the activity is readily perceptible in in vivo PK/PD studies that have established that the human-simulated regimen of cefepime/zidebactam combination elicits a potent 2–3-log kill of OXA-carbapenemases expressing A. baumannii in neutropenic murine lung/thigh infection even against strains with MIC up to 64 mg/l ( Moya et al., 2017 ; Avery et al., 2018 ; Almarzoky Abuhussain et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%